Video documental sobre el derecho a la jubilación de los trabajadores no remunerados del hogar en el Ecuador. - Arévalo Naranjo, Amira Belén (2016)
This communication project presented in documentary format video lasts 23 minutes 19 seconds. Its centerpiece is the right of access to the retirement of unpaid workers home, with an emphasis on information on the benefits and claim the work at home doing housewives with an economic recognition through Security Social. Besides the benefits that can access short and medium term, including the insurance death montepío retirement and disability insurance, which consists of an annuity in case of total or absolute permanent disability it is collected. In the communication project steps for the documentary in its all stages are set, until the final product ready for distribution. The production of this documentary takes as its starting point a qualitative research with the background that led to the adoption of the Law on labor justice and recognition of unpaid household as a productive exercise for society, contrasted with testimonials from real cases on the said Act. The product also has a socio-political analysis on the debate of the Law on the National Assembly and its main actors criteria. Thus what is intended with the documentary is to show the importance of having a legal framework that protects people, in this case, affiliated to the social security in old age.